Evaluating experimental drill on deployment of military emergency medical team for disaster relief - Luong, Trung Hieu; Nguyen, Nhu Lam; Hoang, Hai; Nguyen, Tien Dung; Tran, Dinh Hung; Ngo, Minh Duc; Nguyen, Dai; Nguyen, Thanh Chung; Le, Quang Thao; Nguyen, Thai Ngoc Minh (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Objective: To evaluate the results of implementing the Military Medical Team model for natural disasters.Subjects and methods: Organizing an experimental drill of simulated earthquake situations with 25 trauma victims and 5 cases of chronic illness. The evaluated content included the implementation of military medical stations and Medical response at military medical stations in terms of admission, triage, emergency care, and transferring.Results: The deployment of the military medical station for disaster relief met the requirements of over 80%. The management of the team leaders, the members' activities, proficiency in using equipment and forms, as well as coordination were sufficient > 95%. The triage results using START met the scenario requirements from 87.5% and over. All contents of operation achieved 90% or more.Conclusion: The drill met the set requirements; some contents were added to complete the model.